Assessment of Tree Diversities in Oban Division of the Cross River National Park (CRNP), Nigeria (2013)
Many tropical forests are under great anthropogenic pressure and require management intervention to maintain the overall biodiversity, productivity and sustainability. This cannot be possible without proper understanding of their structure and species diversities. Tree diversity in Oban Division of the CRNP was assessed. Systematic sampling technique was adopted for plot locations. Two transects, 2km long with a distance of 600m apart were cut in each of the three study sites. Four plots of 50m><50m were laid alternately along each transect at 500m intervals in the closed canopy and secondary forests. Forty-eight plots were used for the study. Tree growth parameters were measured on all the trees with Dbh>10cm within each plot. All the measured trees were identified and classified into their respective families. Species diversity indices were computed for the trees in the two forest types. The canopy layer to which each tree belongs was noted. Data were analyzed using descriptive statistics, Diversity Indices, t-test as well as analysis of variance. A total of 118 species (107 genera and 37 families) of trees were recorded, with 72 and 69 species in the closed canopy and secondary forests respectively. The Strombosia spp. was the most abundant species in the forests. The family, Olacaceac accounted for 11.94% of the total individuals recorded in the area. This was followed by Mimosoideae (8.4%). The average tree stems/ha was 158 and 130 in the closed canopy and secondary forest respectively. The Simpson’ Indices were 0.99 and 0.98 for the two forest types respectively, which implied high floristic richness The Shannon-Wiener’s Indices (4.36 and 4.14) and the equitability ratios (0.9513 and 0.9506) were high for the two forest types, which indicated moderate representation of most of the species in the area. The tree growth parameters significantly differ under different canopy layers (P<0.05). However, most of the parameters were not significantly different in the two forest types fP>0.05)